Integration of Agricultural Research Planning and Its Implementation to Improve Food Security Through Development of Agricultural Research Information System (SIPP) - Dian Wisika Prajanti, S; Wilonoyudho, S; Ahmadi, F; Oktavilia, S (KnE Social Sciences, 2018)
Food security has broader dimensions and involves many development sectors. The success in food security development is not only determined by the performance of one sector but also that of the others. Thus, synergies between sectors, academicians, agricultural business actors, governments and society are highly necessary as the key success of food security development. This research aims to conduct an implementative study on integrating research planning which may result in sustainable food security improvement. Many researches have been repeatedly conducted, yet various results have not been implemented due to the lack of sufficient and accessible information. In addition, accesses to primary data tend to be expensive and difficult to obtain which result in relatively slow development of agriculture and food researches. Thus, this research is conducted in order to integrate all food security sectors through the development of Information and Communication Technology (ICT) by creating an Agricultural Research Information system (SIPP). The results show that rapid and precise information in agricultural research integration may improve research information which may result in more responsive and accurate research implementation. Agricultural research information, such as planning, information mapping of agricultural product commodity prices that farmers may determine where they may sell their agricultural products to generate greater benefits. In addition, other information, such as weather conditions, seeds, postharvest agricultural commodities, and etc, may also be easily obtained to support the agricultural development. The agricultural information integration may be obtained by establishing an agricultural research information system through Information Technology (IT) to connect researches with academicians, development, central government, local governments, and agricultural institutions as well. Capacity building through ICT in agricultural researches provides new areas in model implementations to improve researches through ICT technology for those researchers in the field of agriculture. Keywords: Integration, Food Security, Planning, Mapping, Agricultural Research Information System.